2020
DOI: 10.3390/ijerph17218019
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Experiences of Emotional Labor and Workplace Violence that Are More Harmful to Health in Korean Workforce?

Abstract: (1) Background: This study aims to investigate the impact of emotional labor and workplace violence on sleep disturbance, depression, and health status in workers. (2) Methods: Data from 34,742 participants of the 2011–2014 Korean Working Conditions Survey were included in this study. We compared the incidence of sleep disturbance, depression, and health status according to emotional labor and workplace violence and used logistic regression to analyze factors that affect health status. (3) Results: Emotional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…In the Sixth EWCS, workers reported experiencing verbal abuse, threats, physical violence, and sexual harassment at 12%, 4%, 2%, and 1%, respectively (Eurofound, 2017). The results of this study showed a lower prevalence of WPV compared with the results of EWCS; however, there was no improvement compared with results of the 2011-2014 KWCS (Hwang et al, 2020). The methodology and questionnaire used in the KWCS were the same as those used in the EWCS.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In the Sixth EWCS, workers reported experiencing verbal abuse, threats, physical violence, and sexual harassment at 12%, 4%, 2%, and 1%, respectively (Eurofound, 2017). The results of this study showed a lower prevalence of WPV compared with the results of EWCS; however, there was no improvement compared with results of the 2011-2014 KWCS (Hwang et al, 2020). The methodology and questionnaire used in the KWCS were the same as those used in the EWCS.…”
Section: Discussionmentioning
confidence: 61%
“…Consistent with previous studies (Lu et al, 2019;Saberi et al, 2019), the highest rates of violence in the KWCS were verbal abuse and the lowest rates were from physical violence. This is significant because both verbal and physical violence have been reported to be associated with poor health status (Hwang et al, 2020;Pien et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial hazard of work is assessed only in the context of the organization's activities for the production and synthesis of chemicals and is not considered as a single risk factor for all types of work. In some cases, the psycho-emotional reward for the employee is assessed (Hwang et al, 2020;Taouk et al, 2020).…”
mentioning
confidence: 99%